Antimicrobial Resistance Analysis of Clinical Escherichia coli Isolates in Neonatal Ward - Wu, Dan; Ding, Yijun; Yao, Kaihu; Gao, Wei; Wang, Yajuan (Frontiers in Pediatrics, 2021)
Background Escherichia coli (E.coli) column for one of the most common pathogens causing neonatal infections. The emergence of antibiotic-resistant bacteria is a major cause of treatment failure in infected newborns. The purpose of this study was to describe antibiotic and multidrug resistance of E.coli strains isolated from neonates with infection throughout the years 2009-2011. Methods The antimicrobial susceptibility testing of E.coli strains to selected antibiotics was assessed using the E-test technique on the Mueller-Hinton agar. The antimicrobial tests included ceftazidime, cefuroxime, cefatriaxone, amoxicillin, amoxicillin-clavulanic acid, cefoperazone- sulbactam, meropenem, gentamicin, ciprofloxacin, and sulfonamides. Results A total of 100 E.coli strains were isolated from sputum (n = 78), blood (n = 10), cerebrospinal fluid (n = 5), and umbilical discharge (n = 7) samples of hospitalized neonates at the Beijing Children’s Hospital. The highest rate of E.coli resistance was found in amoxicillin (85%), followed by cefuroxime (65%) and cefatriaxone (60%), respectively. A total of 6% and 5% of all isolates were only resistant to amoxicillin/clavulanic acid and cefoperazone -sulbactam. The rates of resistance to ceftazidime, gentamicin, ciprofloxacin, and sulfonamides were 31%, 20%, 33%, and 47%, respectively. All isolates were susceptible to meropenem. Approximately 26% of all E.coli isolates were multidrug-resistant. The detection rate of ESBL-Producing E.coli was 55%. Conclusions Multi-drug-resistant E.coli has become an important and complex problem in clinical treatment, and it is thus essential to monitor E.coli resistance in neonates.